Oral Health Related Quality of Life and Xerostomia in Cardiovascular Patients - Tabesh, Adel; Karimzadeh, Hossein; Shahriari, Narges; Fakheran Esfahani , Omid (Galen Medical Journal, 2025)
Background: Cardiovascular patients frequently suffer from xerostomia and several modalities has been tried to alleviate the symptom. Improving Oral Health Related Quality of Life (OHRQoL) is a subjective index and considered as the final achievement in oral treatments. The aim of the present study was to evaluate OHRQoL in these patients, as well as its relation to xerostomia and some other factors. Materials and Methods: In this cross-sectional study, 244 patients participated. OHRQoL was assessed by Oral Health Impact Profile 14 (OHIP-14). Xerostomia severity was quantified by the Xerostomia Inventory (XI). Consumed anti-hypertensive drugs, age and gender were also recorded. Data were analyzed using SPSS 22 (IBM version 22.0, Chicago, USA) and statistical significance level was considered P<0.05. Results: The mean age of participants was score of OHIP-14 was 58.90 ± 5.66 years, of whom 53% were male and 47% female. The mean total OHIP-14 score was 13.33 ± 11.11. Patients with xerostomia consisted 78% of the sample, with a mean XI score of 23.9 ± 5.1. Total and all domain scores of OHIP-14 were directly and significantly correlated with XI score (P<0.001). Also, age had a direct and significant correlation with both OHIP-14 (P<0.001) and XI (P=0.001) scores. Use of cardiovascular drugs was not significantly related to xerostomia presence or severity (P>0.05). Conclusion: The majority of cardiovascular patients suffer from moderate xerostomia, regardless to the type of medication they consume. Xerostomia affects OHRQoL in these patients and should be treated properly to improve their life quality, especially among the elderly.